Performance, carcass characteristics and litter moisture in broilers housed at two densities - Gopinger, Edenilse; Avila, Valdir Silveira De; Perondi, Dani [UNESP]; Catalan, Aiane Aparecida Da Silva; Krabbe, Everton Luis; Roll, Victor Fernando Büttow (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
The effect of stocking density in broiler chickens (11.08 and 13.20 birdsm-2), between 5 and 45 days of age, was assessed with regard to performance, cut yield, litter moisture and frequency of pododermatitis injuries. Further, 476 one-day chicks Cobb 500(r) were distributed in a completely randomized design at two densities (birds m-²), with seven replications per treatment in 14 experimental units. Birds housed at a lower density (11.08) increased feed intake (p < 0.05), without any effect on weight gain and feed conversion. Retail yields were not influenced (p > 0.05) by treatments. In the case of higher density (3.20) the litter showed higher moisture content (p < 0.05) at 28 and 35 days of age. There was a higher occurrence of pododermatitis in birds housed at a density of 13.20 birds m-2. Results show that increased housing density from 11.08 to 13.20 birds m-2 does not affect growth performance, carcass yield and cuts. However, a housing density of 13.20 birdsm-2 increased litter moisture and provided a higher occurrence of grade I pododermatitis.

Foi realizado um experimento para verificar o impacto da densidade de alojamento em frangos de corte (11,08 e 13,20 aves m-2) sobre o desempenho, rendimento de cortes, umidade da cama e frequência de lesões por pododermatite no período de cinco a 45 dias de idade. Foram utilizados 476 pintos da linhagem Cobb500(r) com um dia de idade, distribuídos em um delineamento experimental inteiramente casualizado, empregando duas densidades (avesm-2) e sete repetições por tratamento, 14 unidades experimentais. Observou-se que as aves alojadas em menor densidade (11,08) apresentaram maior consumo de ração (p < 0,05), porém, sem afetar o ganho de peso e a conversão alimentar. O rendimento das partes não foi influenciado pelos tratamentos (p > 0,05). Foi verificado efeito significado (p < 0,05) sobre a umidade da cama na maior densidade (3,20), apresentando maior umidade (p < 0,05) aos 28 e aos 35 dias de idade das aves. Observou-se maior incidência por pododermatite em aves alojadas na maior densidade (3,20). Conclui-se que o aumento da densidade de alojamento de 11,08 para 13,20 aves m-2, não afeta o desempenho zootécnico, rendimento da carcaça e cortes. Porém, promoveu aumento na umidade na cama, assim como a maior incidência de pododermatite de grau 1 foi observada na densidade de 13,20 avesm-2.
Desempenho, características de carcaça e umidade da cama em frangos decorte alojados em duas densidades
Keywords: chickens; feed intake; stocking; environment; pododermatitis; welfare; aves; consumo de ração; lotação; ambiência; pododermatite; bem-estar